PENGEMBANGAN MODUL TRIGONOMETRI BERBASIS CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS MAHASISWA (Universitas PGRI Sumatera Barat, 2021)
Â Insufficient and supportive teaching materials for students' mathematical creative thinking skills in the trigonometry course as the background of this research, with the aim of producing quality CTL-based trigonometry modules by paying attention to terms of validity, module practicality, effectiveness in terms of students' mathematical creative thinking abilities. The development of this module uses the ADDIE stages (analysis, design, development, implementation, evaluation). The research subjects are second semester students in the 2020/2021 academic year UNRIKA at Mathematics Education study program. Data were obtained from instruments in the form of a standard questionnaire for assessing teaching materials from BSNP to measure validity, student response questionnaires to measure practicality, and mathematical creative thinking ability test questions to measure effectiveness. Based on the results of the study, the percentage of achieving module validity from the assessment of material experts is 87.75% and media experts is 96.25%. These results are classified as very valid. For the practical aspect, the percentage of student response questionnaire achievement is 85.75% with a very good category. However, the module was declared to be not effective enough seen from the results of the mathematical creative thinking ability test which showed an average score of 68.25 with a complete learning outcome of 50%.